(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2017)
The main aim of article is to discuss the position of Middle Pomerania with regard to the national strategic documents (relating to regional and spatial policy) and the current programming period of the EU (2014-2020). The aim was achievied through the analysis of national strategic documents (The nationalspatial development concept 2030; The national strategy for regional development2010-2020), data of Central Statistical Officeand data of co-financing from the EU for Poland in the years 2014-2020. The newly created Middle Pomerania voivodeship could be found among the regionswith a high level of co-financing from the EU andthe funds would be channeled towards areas of real needs.